Randomized controlled clinical trial of long-term chemo-mechanical caries removal using PapacarieTM gel - Lara Jansiski MOTTA; Sandra Kalil BUSSADORI; Ana Paula CAMPANELLI; André Luis da SILVA; Thays Almeida ALFAYA; Camila Haddad Leal de GODOY; Maria Fidela de Lima NAVARRO (University of São Paulo, 2014)
Objectives: Compare the effectiveness of PapacarieTM gel for the chemo-mechanical removal of carious lesions on primary teeth to conventional caries removal with a low-speed bur with regard to execution time, clinical aspects and radiographic findings. Material and Methods: A randomized controlled clinical trial with a split-mouth design was carried out. The sample was composed of 20 children aged four to seven years, in whom 40 deciduous teeth were randomly divided into two groups: chemo-mechanical caries removal with PapacarieTM and removal of carious dentin with a low-speed bur. Each child underwent both procedures and served as his/her own control. Restorations were performed with glass ionomer cement. The time required to perform the procedure was also analyzed. The patients underwent longitudinal clinical and radiographic follow-up of the restorations. Results: No statistically significant difference between groups was found regarding the time required to perform the procedures and the radiographic follow up. Statistically significant differences between groups were found in the clinical evaluation at 6 and 18 months after treatment. Conclusion: PapacarieTM is as effective as the traditional method for the removal of carious dentin on deciduous teeth, but offers the advantages of the preservation of sound dental tissue as well as the avoidance of sharp rotary instruments and local anesthesia.